2023
DOI: 10.14744/hf.2022.2022.0042
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the etiology of chronic liver disease by referral to a FibroScan center: Increasing prevalence of the nonalcoholic fatty liver disease

Abstract: Background and Aim: Chronic liver disease (CLD) is a leading cause of morbidity and mortality worldwide with a wide etiological spectrum. Fi-broScan ® is used for follow-up of fibrosis and steatosis. This single-center study aims to review the distribution of indications by referral to Fi-broScan ® .Materials and Methods: Demographic characteristics, CLD etiologies, and FibroScan ® parameters of the patients who were referred to our tertiary care center between 2013 and 2021 were retrospectively evaluated.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This clearly shows that NAFLD has emerged as the leading cause for CLD and cACLD in current times. This is also supported by a recent FibroScan‐based study by Eris et al, which similarly reported NAFLD as the leading etiology of liver fibrosis at their center 26 . It is important to highlight as NAFLD can continue to contribute to liver disease progression in patients with other etiologies of CLD, which have been adequately treated 10,27–29 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This clearly shows that NAFLD has emerged as the leading cause for CLD and cACLD in current times. This is also supported by a recent FibroScan‐based study by Eris et al, which similarly reported NAFLD as the leading etiology of liver fibrosis at their center 26 . It is important to highlight as NAFLD can continue to contribute to liver disease progression in patients with other etiologies of CLD, which have been adequately treated 10,27–29 .…”
Section: Discussionmentioning
confidence: 68%
“…This is also supported by a recent FibroScan-based study by Eris et al, which similarly reported NAFLD as the leading etiology of liver fibrosis at their center. 26 It is important to highlight as NAFLD can continue to contribute to liver disease progression in patients with other etiologies of CLD, which have been adequately treated. 10,[27][28][29] Notably, NAFLD-associated HCC is also markedly on the rise, concurrent with the rise in prevalence of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the probe was carried out using an automated selection tool, choosing either the M (frequency: 3.5 Hz) or XL (frequency: 2.5 Hz) probe as required. [ 11 , 12 ] To determine LSM for each patient, a series of 10 consecutive valid measurements were taken (interquartile range-to-median ratio ≤0.3), and the median value was recorded. [ 11 , 12 ] The CAP is an algorithm that relies on the attenuation of ultrasound waves and is accessible through the FibroScan ® system.…”
Section: Methodsmentioning
confidence: 99%
“…[ 11 , 12 ] To determine LSM for each patient, a series of 10 consecutive valid measurements were taken (interquartile range-to-median ratio ≤0.3), and the median value was recorded. [ 11 , 12 ] The CAP is an algorithm that relies on the attenuation of ultrasound waves and is accessible through the FibroScan ® system. [ 13 , 14 ] In each patient, CAP values were obtained concurrently with LSM values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation